2015
DOI: 10.3389/fneur.2015.00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blast Overpressure on Neurons and Glial Cells in Rat Organotypic Hippocampal Slice Cultures

Abstract: Due to recent involvement in military conflicts, and an increase in the use of explosives, there has been an escalation in the incidence of blast-induced traumatic brain injury (bTBI) among US military personnel. Having a better understanding of the cellular and molecular cascade of events in bTBI is prerequisite for the development of an effective therapy that currently is unavailable. The present study utilized organotypic hippocampal slice cultures (OHCs) exposed to blast overpressures of 150 kPa (low) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 157 publications
(220 reference statements)
4
36
0
Order By: Relevance
“…However, we focused our analyses on the vigorous early astrocytic response to blast overpressure that was not previously reported. In our earlier studies we demonstrated robust activation of astrocytes at 72 h post injury, however at that time point we detected only a small number of dead astrocytes [34]. Though, corresponding to our current results, we observed dead microglial cells at 4 and 24 h post-injury [34].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, we focused our analyses on the vigorous early astrocytic response to blast overpressure that was not previously reported. In our earlier studies we demonstrated robust activation of astrocytes at 72 h post injury, however at that time point we detected only a small number of dead astrocytes [34]. Though, corresponding to our current results, we observed dead microglial cells at 4 and 24 h post-injury [34].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study we analyzed cellular changes in OHCs at 2 h following blast exposure, as under the same conditions we previously observed dramatic increase in cell death from 0 to 2 h post-injury [34]. At 2 h post-injury, in addition to dead astrocytes we also observed dead neurons and microglial cells (data not shown).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations